Halfway to Amarillo [videorecording (DVD)] - Binder, Burt; Giles, Peter; Jones, Luke; Smith, Lindsey G.; Michaels, Felicia (Gravitas Ventures, 2023)
Michael Coleman is working on a novel that will make or break his career. Halfway through, he completely loses the plot and comes down with a devastating case of Writer's Block. At his lowest point, the main character from his novel, an outlaw named Eli West, leaps out of the novel and throws a wrench into Michael's life. As if that isn't bad enough, the villain of the novel, a crooked sheriff named Morgan Ambrose, follows in quick pursuit.